Molecular Identification of Phlebotominae Sand Flies (Diptera: Psychodidae) in Al-Diwaniyah Region/Iraq - Hadi M.H. Al-Mayali (Journal of Global Pharma Technology, 2017)
In this study, the  Polymerase chain reaction technique (PCR)  and morphological identification were used in identification of sand flies ,the vectors of leishmaniasisin diseases  in Al-Diwaniyah region for the first time in Iraq,  Morphological  identification  showed presence three different species of sand flies, two belong to Phlebotomusgenus it P.papatasiand P. sergenti and one belong to Sergentomiya genus it S. sintoni. It has been observed that the most species density was the genus P. papatasi (53.09%) followed by the S.sentoni species (28.54%) then  P. sergenti (18.35%). Molecular identification through detection of the   Mitochondrial cytochrome b gene DNA (Cytbgene)   and molecular length output 575base pairs (bp) of species P.papatasi and a molecular length 325 bp of the species of P.sergenti While the species S. sintoni was excluded because it is one of the species that tend to feed on the blood of animals and rarely found indoor and there no indication of its relationship to leishmaniasisin disease in human. Molecular identification results for extracted DNA samples of 2250 sand flies females by PCR method showed two species of sand flies are P.papatasi and  P.Sergenti, P. papatasi species The PCR amplified products showed bands of molecular weights 325 and 575 base pair . Analysis of individual sequences belonging to P. papatasispecies and P.sergenti.Keywords: Molecular identification Phlebotomus, Sand flies, Al-Diwaniyah Iraq.